Acquired immunodeficiency with disseminated cryptococcosis. Issue 3 (March 1986) - Pippard, M J; Dalgleish, A; Gibson, P; Malkovsky, M; Webster, A D
Abstract : A 9 year old Portuguese boy presented with severe wasting and a disseminated cryptococcal infection that resolved after massive doses of intrathecal and parenteral antifungal agents. Clinical and laboratory findings were consistent with AIDS. Apart from neonatal blood transfusions, there were no identified risk factors for HTLV III infection.